Scanning electron microscopy reveals severe external root resorption in the large periapical lesion. Issue 6 (9th March 2016) - Ookubo, Kensuke; Ookubo, Atsushi; Tsujimoto, Masaki; Sugimoto, Kouji; Yamada, Shizuka; Hayashi, Yoshihiko
ABSTRACT: The present study was designed to investigate the relationships between clinicopathological findings and the resorptive conditions of root apices of teeth with periodontitis. The samples included 21 root apices with large periapical radiolucent lesions. The preoperative computed tomography (CT) and intraoperative findings were correlated with the presence, extension, and the progression pattern of periapical resorption using a scanning electron microscope. The subjects' age, gender, chief complaint, type of tooth, percussion test results, size of periapical lesion using CT, and intraoperative findings were recorded. All apicoectomies were performed under an operative microscope for endodontic microsurgery. A significant large size was observed in cystic lesions compared with granulomatous lesions. The cementum surface at the periphery of the lesion was covered with globular structures (2–3 μm in diameter). Cementum resorption started as small defect formations at the surface. As the defect formation progressed, a lamellar structure appeared at the resorption area, and the size of globular structures became smaller than that of globules at the surface. Further resorption produced typical lacuna formation, which was particularly observed in fracture cases. The most morphologically severe destructive pattern of dentin resorption was observed in large cystic lesions. This study is the first report to elucidate the relationships between three clinical types of undesirable periapical lesions: (1) undertreatment, (2) periapical fracture, (3) macro‐level resorption, and the microstructure of external root resorption including from small defects at the cementum surface to a significant destructive pattern inside the dentin. Microsc. Res. Tech. 79:495–500, 2016 . © 2016 Wiley Periodicals, Inc.